Identification of leakage syndrome towards the sustainability of residential buildings In Malaysia - Ishak, N.H.; Che’ Ani, A.I.; Omar, Y.; Ramly, A. (2009)
Tropical nature of Malaysian region suggests that building of this region should be capabled enough to resist the humidity and condensation. The high proportion of annual rain fall in the region makes its building vulnerable to dampness and affects its sustainability. Water leakage problems in most buildings have always been an issue in the daily activities. Until today, continuous remedial works are done to solve this problem. The leakage syndrome is like uncontrollable disease, once it occurs in building at post occupational stage it is almost impossible to get rid of it. The resulting leakage types and its various forms attack the buildings from all sides i.e. from roof to bottom of building and its different form within building envelope and its enclosure. Residential buildings are among major affected building by this syndrome and consume bulk of exchanger on the maintenance of defects caused by building leakage. Unfortunately, the building with such conditions always emerges as the financial burden on the state or quarters concerned. Even in some cases in Malaysia, the maintenance cost of such building reaches at the level of total construction cost. The purpose of this paper is to identify the leakage types, causes of leakage and the affected leakage areas in high rise residential buildings as an earliest action for maintaining the building sustainability.